Recrystallization of biaxially oriented polyethylene film from partially melted state within crystallite networks. (16th March 2020) - Ren, Minqiao; Tang, Yujing; Gao, Dali; Ren, Yueming; Yao, Xuerong; Shi, Hongwei; Zhang, Taoyi; Wu, Changjiang
Abstract: Recrystallization behavior and the final crystallite orientation of biaxially oriented polyethylene (BOPE) film from different melted states have been studied by using differential scanning calorimetry (DSC) and wide-angle X-ray diffraction (WAXD), respectively. WAXD result shows that two kinds of crystallites (1 and 2) with different orientations are aligned around the transverse direction (TD) of the film plane. When BOPE film is annealed in the temperature range of 110~ 125 °C, the residual crystallites 1 are still aligned along the TD, while the residual crystallites 2 are gradually rotated and aligned along the machine direction (MD). Recrystallization of BOPE film from the partially melted states is enhanced and the maximum crystallization peak shifts to higher temperature by 7 °C. The newly formed crystallites after recrystallization are aligned along the TD and MD, respectively. When annealing temperature attains to 128 °C, a trace amount of residual crystallites 1 persists along the TD. The newly formed crystallites after recrystallization are also aligned the TD. When the storing temperature range is in 130–150 °C, the melt memory effect occurs in BOPE film, and it influences crystallization kinetics and the crystallite orientation. Graphical abstract: Left: Variation of the crystallization peak temperature (Tc, peak) as a function of the storing temperature (Ts ) for BOPE film. Right: (a) X-ray pole figure of (200) crystal plane of BOPE film. (b)X-ray pole figure of (200) crystal plane of BOPE film annealed at 125 °C for 5 min and then cooled down to 25 °C. Image 104 Highlights: Crystallites with different orientations are aligned along TD of BOPE film. Recrystallization rate of BOPE film from the partially melted state is enhanced. The newly formed crystallites are aligned along TD and MD, respectively. The melt memory effect influences crystallization and orientation of BOPE film.